The secret of clouds - Richman, Alyson (Berkley, 2019)
"In her second year teaching sixth grade English, Maggie Topper is chosen for a special assignment: to privately tutor a student with serious health issues that prevent him from attending class with other kids. Though she agrees to the assignment, her decision is clouded with painful memories from her own childhood. It isn't easy for her to make a connection with Yuri Krasny, the son of two Ukrainian immigrants, until Maggie uncovers his passion for baseball. As she uses the sport to get Yuri more interested in her lessons, he begins to slowly open up to her. Piece by piece his story comes together, starting back when his mother, a ballerina in Kiev, met an earnest young student hoping for a better future...before a terrible accident changed their lives forever. Yuri's boundless curiosity and unique wisdom inspire Maggie to make difficult changes in her own life. And she'll never realize just how strong Yuri has made her--until she needs that strength the most..." --